Training in electrical canting for children with special needs to improve batik quality - Noni Setyorini; Ika Menarianti; Prianka Ratri Nastiti; Inayatur Rosidah; Daffa Arya Dinata (University of Merdeka Malang, 2023)
“Asal Batik” SMEs help children with special needs by teaching them how to make batik, a traditional cloth. These children often face challenges in society, so this community service program aims to equip them with important batik skills, encouraging independence and inclusiveness. The process of making batik is made simple so that it is easy for children with special needs to follow. However, SMEs involved in batik production face challenges such as limited production scale and insufficient infrastructure. To overcome this problem, this community service introduced electric canting to increase production and facilitate marketing on a larger scale. In addition, support is provided in the form of funds, equipment, and materials to increase overall production capacity. The efforts made by “Asal Batik” SMEs have resulted in positive changes. There has been a marked increase in both production levels and the variety of batik products, thanks to advances in electronic batik equipment which makes it easier for children with special needs to participate. This shows the positive impact of community service in helping children become economically empowered and socially involved.